Perceived Empowering Leadership, Harmonious Passion, and Employee Voice: The Moderating Role of Job Autonomy - Gao, Ang; Jiang, Jing (Frontiers in Psychology, 2019)
Based on self-determination theory, we conceptualized the effect of empowering leadership on employee’s voice via harmonious passion. This paper further explored the moderating effect of job characteristics in voice process, and proposed a moderated mediation model. Using a sample of 674 supervisor-subordinate dyads, we found that (1) empowering leadership was positively related to employees’ harmonious passion and voice behavior, (2) harmonious passion played a mediating role in the relationship between empowering leadership and employee voice, and (3) job autonomy strengthened the effect of harmonious passion on employee voice, which, in turn, enhanced the mediated relationship between empowering leadership and employee voice via harmonious passion. We discuss the implications of these findings for research and practice.